The Effects of Patient Point of Entry and Medicaid Status on Postoperative Opioid Consumption and Pain After Primary Total Hip Arthroplasty. Issue 14 (15th July 2022) - Schoof, Lauren H.; Mahure, Siddharth A.; Feng, James E.; Aggarwal, Vinay K.; Long, William J.; Schwarzkopf, Ran
Abstract : Introduction: Medicaid expansion has allowed more patients to undergo total hip arthroplasty (THA). Given the continued focus on the opioid epidemic, we sought to determine whether patients with Medicaid insurance differed in their postoperative pain and narcotic requirements compared with privately or Medicare-insured patients. Methods: A single-institution database was used to identify adult patients who underwent elective THA between 2016 and 2019. Patients in the Medicaid group received Medicaid insurance, while the non-Medicaid group was insured commercially or through Medicare. Subgroup analysis was done, separating the private pay from Medicare patients. Results: A total of 5, 845 cases were identified: 326 Medicaid (5.6%) and 5, 519 non-Medicaid (94.4%). Two thousand six hundred thirty-five of the non-Medicaid group were insured by private payors. Medicaid patients were younger (56.1 versus 63.28 versus 57.4 years; P < 0.001, P < 0.05), less likely to be White (39.1% versus 78.2% versus 76.2%; P < 0.001), and more likely to be active smokers (21.6% versus 8.8% versus 10.5%; P < 0.001). Surgical time (113 versus 96 versus 98 mins; P < 0.001) and length of stay (2.7 versus 1.7 versus 1.4 days; P < 0.001) were longer for Medicaid patients, with lower home discharge (86.5% versus 91.8% versus 97.2%; P < 0.001). Total opioid consumption (178 morphine milligram equivalents [MMEs] versus 89 MME versus 82 MME; P < 0.001) and average MME/day in the first 24 hours and 24 to 48 hours (52.3 versus 44.7 versus 44.45; P < 0.001 and 73.8 versus 28.4 versus 29.8; P < 0.001) were higher for Medicaid patients. This paralleled higher pain scores (2.71 versus 2.31 versus 2.38; P < 0.001) and lower Activity Measure for Post-Acute Care scores (18.77 versus 20.98 versus 21.61; P < 0.001). Conclusions: Medicaid patients presenting for THA demonstrated worse postoperative pain and required more opioids than their non-Medicaid counterparts. This highlights the need for preoperative counseling and optimization in this at-risk population. These patients may benefit from multidisciplinary intervention to ensure that pain is controlled while mitigating the risk of continuation to long-term opioid use.